Comparison of viscosity variation formulations for turbulent flow of Al2O3-water nanofluid over a heated cavity in a duct - Abdellahoum, Chahrazed; Mataoui, Amina; Öztop, Hakan Fehmi (Elsevier, 2015)
The viscosity of nanofluid is one of the most critical parameter in nanofluids, which should be considered by researches and need to be investigated thoroughly. This paper compares the several models of the viscosity of turbulent forced convection of Al2O3 nanofluid over a heated cavity in a horizontal duct. It extends the previous work by the same authors by considering several viscosity models on water-Al2O3 nanofluids at small volume particle fraction. The governing equations are discretized by the finite volume method based one point closure of a first order turbulence model. The effects of various parameters such as Reynolds number (1 . 10(4) <= Re <= 1 . 10(5)) and nanoparticles concentration (0 <= phi <= 4%) on the heat transfer and flow characteristics are investigated and discussed. Five different viscosity models (Pack and Cho, Maiga, Einstein, Brinkman and Batchlor) are tested. The results are analyzed through the thermal and dynamical fields with a special interest to the skin friction coefficient and Nusselt number evolutions. It was found average Nusselt number increases with the volume fraction of nanoparticles for the whole range of Reynolds number. As a result, The Einstein, Brinkman and Batchlor viscosity models show similar results and lesser friction and heat transfer. Pack and Cho viscosity model gives maximum friction and heat transfer. (C) 2015 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Water-Al2O3 nanofluid; Viscosity; Separated flows; Turbulence; Forced convection